My virtual escape from patient life: a feasibility study on the experiences and benefits of individualized virtual reality for inpatients in palliative cancer care - Gerlach, Christina; Haas, Laura; Greinacher, Anja; Lantelme, Jonah; Guenther, Melanie; Thiesbonenkamp-Maag, Julia; Alt-Epping, Bernd; Wrzus, Cornelia (BMC palliative care, 2024)
Cancer patients benefit from Virtual Reality (VR) in burdensome situations, but evidence is scarce for palliative situations. Based on earlier work in palliative care, individualized VR interventions like seeing the patient’s home may address a patient’s wish to be at home and thus have a greater effect compared to standard VR content. Yet, some patients and relatives may be concerned about their privacy. Also, patient stakeholders raised concerns about triggering depressed mood or homesickness.